Anisotropic Charge Transport Enabling High‐Throughput and High‐Aspect‐Ratio Wet Etching of Silicon Carbide (Small Methods 8/2022). Issue 8 (17th August 2022) - Shi, Dachuang; Chen, Yun; Li, Zijian; Dong, Shankun; Li, Liyi; Hou, Maoxiang; Liu, Huilong; Zhao, Shenghe; Chen, Xin; Wong, Ching‐Ping; Zhao, Ni
Abstract : Inside Back Cover In article number 2200329, Chen, Zhao, and co‐workers demonstrated an etching structure that exploits anisotropic charge carrier flow to enable high‐throughput, external‐bias‐free wet etching of SiC micro‐/nanostructures with record high etching speed and aspect ratio.